Tráfico de drogas e o princípio da intervenção mínima: aspectos sociais e direitos humanos - Silva, William Trigilio da (Universidade Federal do Tocantins, 2017)
The present dissertation, forged in a bibliographical research, seeks to critically analyze the drug policy in the country. It is known that far from solving the problem the current policy on drug trafficking has contributed to the marginalization of certain social the strength of the penal system. The number of prisoners, due to convictions for trafficking, and the profile of these segregated people (poor and poorly educated), shows that the current model can not reach its goal. Given this mosaic, this research sought to propose a paradigm shift in the treatment of trafficking capable of opposing common sense, reinforcing the idea that the solution of the problem should not necessarily pass through the criminal system and that policies aimed at drug treatment need to be scaled up so that spending is focused on programs for the prevention and treatment of addiction. At the same time it was concluded that the Judiciary should face such a problem, despite the inertia of the legislator. Thus, as long as there is no legislative change capable of adjusting the treatment of drugs, users and traffickers to social reality, it is incumbent upon the director's agent to give interpretative guidelines to current legislation, in order to highlight the humanitarian bias, focused on autonomy and individual freedom, respect for diversity, promotion of ethical and cultural values, whose position will minimize the consequences of repressive policy and contribute to a decrease in incarceration for trafficking